ANALISIS PENGARUH PERTUMBUHAN ASET TERHADAP PENINGKATAN KUALITAS LAPORAN KEUANGAN AUDITAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Anaiza Azlia; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
A company with growing assets will make them hard to control their manager’s action so they need more qualified Public Accounting Firm (KAP). The purpose of this research is to analyze the effect that increase of of company’s size variable shown to affect the increase of the quality of audited financial statements (auditor switching from Non Big 4 to Big 4). This research uses financial statment data of companies listed in Indonesia Stock Exchange (BEI) in the period od 2011-2013. Sample collecting method which used in this research is purposive sampling. 34 companies are used as samples. Hypothesis are tested by logistic regression analysis. The result showed that increase of company’s size variable shown to affect the increase of the quality of audited financial statements.